1998
DOI: 10.1103/physrevlett.80.2382
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Relief of Misfit Strain of Ge/Si(001)

Abstract: The intrinsic stress of the Stranski-Krastanov system Ge͞Si(001) was investigated in the range 700-1050 K. Characteristic stress features indicate that the relief of the misfit strain proceeds mainly in two steps: (i) by the formation of 3D islands on top of the Ge wetting layer and (ii) via misfit dislocations in larger 3D islands and upon their percolation. The temperature dependence of strain relief by 3D islands as well as their nucleation and growth behavior support a kinetic pathway for 3D islanding.[S00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…Based on the fact that the highest stress in an island occurs at the corner where the island meets the substrate, it has been suggested that strain-relieving perfect misfit dislocations are generated at the island edge when the island reaches its critical size. [3][4][5][6] Their generation and morphology have been considered theoretically. [7][8][9] In addition, partial misfit dislocations have been identified in islands by scanning tunnelling microscopy 10 and transmission electron microscopy ͑TEM͒ 11-13 and a recent theoretical study 14 has concluded that partial misfit dislocations are energetically preferred to perfect dislocations in some regions of quantum dots.…”
mentioning
confidence: 99%
“…Based on the fact that the highest stress in an island occurs at the corner where the island meets the substrate, it has been suggested that strain-relieving perfect misfit dislocations are generated at the island edge when the island reaches its critical size. [3][4][5][6] Their generation and morphology have been considered theoretically. [7][8][9] In addition, partial misfit dislocations have been identified in islands by scanning tunnelling microscopy 10 and transmission electron microscopy ͑TEM͒ 11-13 and a recent theoretical study 14 has concluded that partial misfit dislocations are energetically preferred to perfect dislocations in some regions of quantum dots.…”
mentioning
confidence: 99%
“…Further pathways to strain relaxation emerge when the constraint of perfectly coherent heterostructures is dropped. In this case, the formation of point-and particularly line-like defects of the lattice, as vacancies or interstitials and dislocations, can be very efficient ways of releasing the accumulated strain energy [47][48][49]. Here we shall however confine our discussion to the case of strict epitaxial coherence.…”
Section: Strain Relaxation In Heteroepitaxial Flat Layersmentioning
confidence: 97%
“…3 Depending on the surface orientation of Si and substrate temperature (T s ), the critical thickness and the shape of the islands are found to vary. The critical thickness is ~ 3-7 monolayers (ML) for Ge on Si(001) 4 whereas it increases up to 10 ML for (015) surface. 5 The 3D islands can be of different shapes like triangular on Si(111) 6 , rectangular on Si(001) (at T s = 700°C) 4 and hut clusters on Si(015).…”
Section: Introductionmentioning
confidence: 99%
“…The critical thickness is ~ 3-7 monolayers (ML) for Ge on Si(001) 4 whereas it increases up to 10 ML for (015) surface. 5 The 3D islands can be of different shapes like triangular on Si(111) 6 , rectangular on Si(001) (at T s = 700°C) 4 and hut clusters on Si(015). 5 Bimodal distribution of the islands were also observed for the Ge film prepared on Si(001) at a T s of 600°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation